Relationship of Religious Attitude and Self-control with Quality of Life among the Students of University of Qom and Qom University of Medical Sciences: A Path Analysis - Susan Bahrami (Health, Spirituality and Medical Ethics, 2019)
Background and Objectives: Quality of life is a key component of health, associated with the individual and social living conditions of a person. Religious or spiritual parameters are among the most important determinants of quality of life (QOL) and its outcomes, and they are more significant and effective when the university students are involved. Therefore, the present study was conducted to evaluate religious attitude and self-control among the students of University of Qom and Qom University of Medical Sciences in Qom, Iran. This study was also targeted toward evaluating the relationship between these variables and QOL in the same population. Methods: This cross-sectional study was conducted on 298 students selected through multistage stratified random sampling technique. The participants’ religious attitude, self-control, and QOL were assessed based on the questionnaires of 40-point, 24-point, and 26-point scales, respectively. The data were analyzed through path analysis using the SPSS (version 20) and Mplus software. Results: Out of 298 participants, 160 (54%) respondents were the students of Qom University of Medical Sciences, and 178 (60.3%) students were female. According to the results, religious attitude showed a positive correlations with QOL and self-control. The results of path analysis revealed that religious attitude had an indirect effect on QOL through affecting self-control, in addition to a direct effect on QOL. The overall effect of religious attitude on QOL was estimated at 0.372, while the effect of self-control on QOL was reported as 0.449. Conclusion: As the fidnigns indicated, the promotion of religious attitudes can improve self-control, thereby leading to the improvement of QOL.